Induksi Kalus Pisang Barangan Merah Musa acuminata Colla dengan Kombinasi Hormon 2,4-D dan Bap Secara In Vitro - Andi Ilham Latunra (Universitas Hasanuddin, 2017)
Research on callus induction of red banana Musa acuminata Colla with combination hormone 2,4-D and BAP in vitro aims to find a combination of hormones BAP and 2,4D were effective in inducing callus red banana. This study was conducted from February until April 2016 at Tissue Culture Laboratory Research and Development Center of Biotechnology, Hasanuuddin University, Makassar. Callus was induced from leaf explants red banana from the in vitro culture of a 5 month old, the basic medium MS + 2,4-D + BAP. This designs uses in completely randomized design with 4 treatments with 3 repetitions. The combinations were : MS medium + 1 ppm 2,4-D + 4 ppm BAP (W1), MS medium + 2 ppm 2,4-D + 3 ppm BAP + (W2), MS medium +3 ppm 2,4 -D + 2 ppm BAP (W3) and MS medium + 1 ppm 2,4-D + 4 ppm BAP (W4). Parameters observate in this study were the emergence of callus and percentage appears callus, callus color, texture callus, and callus wet weight. The results showed that the combination of MS medium + 2 ppm 2,4D + 3 ppm BAP (W2) is the best medium to induce callus, marked by green callus, compact callus (friable), and the highest wet weight of callus 0.0203 g.